2007
DOI: 10.1177/10717919070130041001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cognitive Style and Risk Preference on Entrepreneurial Self-Efficacy and Entrepreneurial Intentions

Abstract: The purpose of the current study is to address the distinctive roles of cognitive style and risk preference on four types of entrepreneurial self-efficacy and entrepreneurial intentions. More specifically, we examine how both cognitive style and risk preference separately and interactively contribute to an individual's assessment of his/her own skills and abilities as well as to his/her own entrepreneurial intentions. This study investigated these relationships using an international sample of 528 entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
257
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 351 publications
(284 citation statements)
references
References 40 publications
17
257
2
8
Order By: Relevance
“…Mills and Pawson's (2012) literature survey confirmed that risk-taking is a critical variable for understanding enterprising behaviour, and they IJGE 7,1 consider the variable to be a cornerstone of any decision to start a business. This is consistent with other previous research that has demonstrated a significant relationship between risk tolerance and entrepreneurial behaviour (Barbosa et al, 2007;Karakowsky and Elangovan, 2001;Keh et al, 2002;Sitkin and Pablo, 1992;Sitkin and Weingart, 1995). One reason businesses are launched may be because of the naive view of involved risks: "If entrepreneurs would carefully calculate all the risk involved in starting a new venture, most new ventures would never be started" (Busenitz, 1999, p. 337).…”
Section: Theory and Hypotheses Risk Perceptions Entrepreneurship Andsupporting
confidence: 88%
See 3 more Smart Citations
“…Mills and Pawson's (2012) literature survey confirmed that risk-taking is a critical variable for understanding enterprising behaviour, and they IJGE 7,1 consider the variable to be a cornerstone of any decision to start a business. This is consistent with other previous research that has demonstrated a significant relationship between risk tolerance and entrepreneurial behaviour (Barbosa et al, 2007;Karakowsky and Elangovan, 2001;Keh et al, 2002;Sitkin and Pablo, 1992;Sitkin and Weingart, 1995). One reason businesses are launched may be because of the naive view of involved risks: "If entrepreneurs would carefully calculate all the risk involved in starting a new venture, most new ventures would never be started" (Busenitz, 1999, p. 337).…”
Section: Theory and Hypotheses Risk Perceptions Entrepreneurship Andsupporting
confidence: 88%
“…Knowledge of the relationship between self-efficacy and risk perception in start-up decisions is limited (Barbosa et al, 2007;Krueger and Dickson, 1994;Zhao et al, 2005). In the present study, we suggest that risk perceptions could be a key variable in the nomological network of perceptional variables that influence the start-up decision.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Thompson (2009) did not specify a time frame in the items composing his entrepreneurial intent scale, and he explained why in his study. The lack of a time frame for intentions is also reflected in the measures used by a number of other published entrepreneurial intent studies (e.g., Barbosa et al, 2007;Krueger et al, 2000;Obschonka, Silbereisen, and Schmitt-Rodermund 2010). However, future research could address the issue of time frames by collecting longitudinal data to show whether business creation actually follows entrepreneurial intent, and if so, how long the typical lag is between the formation of substantial intent and actual business founding.…”
Section: Limitations and Future Researchmentioning
confidence: 99%